Pengembangan Pendidikan multikultural di Indonesia melalui lensa filsafat islam - Nurlita, Fara; Maulana, Hikmal; Miskiyya, Eitna Lyana; Latassha, Kevinna Lyora (CV. Kurnia Grup, 2024)
Multicultural education is an educational approach that values cultural diversity and provides equal opportunities for all individuals, regardless of cultural, ethnic, or religious backgrounds. This concept aims to create awareness of the importance of tolerance, respect for differences, and building social harmony amidst diversity. In the context of Islamic educational philosophy, multicultural education can be seen as an effort to realize social justice and balance rooted in Islamic principles, such as brotherhood, justice, and equality. Islamic educational philosophy emphasizes the importance of holistic human potential development, both in intellectual, moral, and spiritual aspects, which aligns with the values of multiculturalism. The urgency of implementing multicultural education in Indonesia is highly relevant in the development of nationalism, especially considering that Indonesia is a country with great diversity in terms of ethnicity, religion, and culture. Multicultural education can be an important instrument for strengthening national unity, reducing the potential for intergroup conflicts, and building awareness of an inclusive national identity. In this context, multicultural education plays a role in fostering mutual respect among ethnic and religious groups, as well as promoting nationalism based on appreciation of diversity. The implementation of multicultural education in Indonesia has been carried out through various policies and educational programs. The curriculum in schools has begun to integrate multicultural values, such as tolerance, cooperation, and respect for differences. Additionally, extracurricular activities and cross-cultural programs have also been developed to encourage students to interact with individuals from different cultural backgrounds. However, the implementation of multicultural education in Indonesia still faces various challenges. One of the main challenges is the resistance from groups who feel that multicultural education can threaten certain identities and cultural values. In addition, there are still educational gaps in various regions, which result in a lack of understanding of the importance of multiculturalism in some areas. To address these challenges, several proposed solutions include enhancing training for educators on the importance of multiculturalism and how to integrate it into the teaching and learning process. In addition, there needs to be closer cooperation between the government, educational institutions, and the community to create an inclusive learning environment that values diversity. Policies that support multicultural education also need to be strengthened, including in terms of providing adequate resources for schools in remote areas. From a philosophical perspective, multiculturalism is seen as a manifestation of the recognition and respect for essential human diversity. Islamic philosophy, in particular, emphasizes the importance of living in harmony amidst differences and teaches that all humans are created equal in the eyes of God, despite having different backgrounds. This principle serves as an important foundation for multicultural education that seeks to build bridges between various community groups.